Enhancement Drip Dose Infusion Accuracy Based on Optocoupler and Microcontroller Sensor - Yudistira Marsya Puvindra; Arief Marwanto; Eka Nuryanto Budisusila; Vugar Abdullayev (International Journal of Advanced Health Science and Technology, 2022)
Setting the speed of infusion drops in a manual manner is by adjusting the clamp on the infusion set, where the nurse must count the number of infusion drops in the chamber at the same time as looking at the time on the watch. This makes the setting is subjective and cannot be shown with numbers. In addition, nurses cannot monitor the infusion rate continuously. Therefore, it is necessary to enhancement the accuracy of giving infusion drops so that they can be objective and can be shown with numbers and monitor continuously. This enhancement in accuracy is done by making a instrument with an optocoupler to detect infusion drops. For processing uses an arduino microcontroller to be the speed and the volume of infusion and detects changes in the rate of infusion drops significantly. And for the display uses a OLED display and a buzzer as an indicator. The results of this instrument, it can be seen that the optocoupler can detect infusion drops in the infusion set properly. This good sensor reading has implications for accurate readings of the infusion drop rate and infusion drop volume. This enhancement in accuracy is not only for the macro drip (20 drops/cc) but also for the micro drip (60 drops/cc). The accuracy of volume readings ranges from 95-99% for the macro drip and 94.5-97% with the micro drip. And for speed accuracy ranges from 92.37-98.46%. Based from the results of this test, enhancement the accuracy of the infusion drip dose administration can be done by making a patient infusion drip dose calculator. This equipment uses an optocoupler sensor, arduino microcontroller, OLED display and buzzer. With the use of this instrument, nurses can be more accurate in regulating the rate of infusion drops given to patients and can monitor it continuously if there is a significant change in infusion rate.